2023
DOI: 10.1097/hjh.0000000000003487
|View full text |Cite
|
Sign up to set email alerts
|

Targeting temperature-sensitive transient receptor potential channels in hypertension: far beyond the perception of hot and cold

Abstract: Transient receptor potential (TRP) channels are nonselective cation channels and participate in various physiological roles. Thus, changes in TRP channel function or expression have been linked to several disorders. Among the many TRP channel subtypes, the TRP ankyrin type 1 (TRPA1), TRP melastatin type 8 (TRPM8), and TRP vanilloid type 1 (TRPV1) channels are temperature-sensitive and recognized as thermo-TRPs, which are expressed in the primary afferent nerve. Thermal stimuli are converted into neuronal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 255 publications
(356 reference statements)
0
1
0
Order By: Relevance
“…Upon administering treatment to 16-week-old SHR rats, the findings indicated that the RTX intervention group elicited a significant reduction in mean arterial pressure when compared to the carrier control group [27]. Furthermore, the thermosensitive receptors, TRPA1/TRPM8/TRPV1, which are expressed in the cardiovascular system, have been implicated in the pathogenesis of hypertension [186]. The distinct activation and deactivation processes of these channels suggest a potential signaling pathway that could pave the way for the development of novel therapeutic strategies for hypertension and associated vascular disorders in the future.…”
Section: Trpv Channelsmentioning
confidence: 99%
“…Upon administering treatment to 16-week-old SHR rats, the findings indicated that the RTX intervention group elicited a significant reduction in mean arterial pressure when compared to the carrier control group [27]. Furthermore, the thermosensitive receptors, TRPA1/TRPM8/TRPV1, which are expressed in the cardiovascular system, have been implicated in the pathogenesis of hypertension [186]. The distinct activation and deactivation processes of these channels suggest a potential signaling pathway that could pave the way for the development of novel therapeutic strategies for hypertension and associated vascular disorders in the future.…”
Section: Trpv Channelsmentioning
confidence: 99%